A study on revolute joints in 3D-printed non-assembly mechanisms. Issue 6 (17th October 2016) - Wei, Xiangzhi; Tian, Yaobin; Joneja, Ajay
Abstract : Purpose: The purpose of this paper is to explore a new design for the journal of revolute joints that can improve the dynamic performance of 3D printed non-assembly mechanisms. Design/methodology/approach: The design improves upon previous proposed designs that use drum-shaped journals in place of cylindrical ones. The authors introduce an innovative new worm-shaped journal. The authors also propose a systematic and efficient procedure to identify the best parameter values for defining the exact shape of the journal. Using three different mechanisms for the experiments, the paper constructs 3D computer-aided design (CAD) models using the design as well as cylindrical and drum-shaped designs. The parameters for the optimum geometry for each type of design are determined by dynamic simulation using the CAD system. Actual prototypes of the ideal designs are constructed using a commercial fused deposition modeling (FDM) machine for physical comparisons. Findings: This paper shows that in simulations as well in physical models, the proposed design outperforms the previous designs significantly. Research limitations/implications: This study was mainly focused on the FDM process, and the authors have not yet explored other processes. One limitation of this approach is that it requires the mechanism to be printed along the axial direction of the revolute joint. Originality/value: This paper proposes a new design for the journal in 3D printed revolute joints. A clear advantage of the design is that it can easily be used to replace normal revolute joins in non-assembly models without affecting any other parts of the geometry. Therefore, with relatively little effort, the authors can print non-assembly mechanisms with improved dynamic performance.